Perceived parenting styles, adolescents' self-esteem and achievement motivation - Abdul Sattar, Nadheema (Institute of Education, International Islamic University Malaysia, 2012)
The study examined parenting styles, self-esteem and achievement motivation to determine if there was a significant relationship between parenting styles and adolescents' self-esteem and achievement motivation. The study employed survey method and data were collected using adapted questionnaires which measured parenting styles, self-esteem and achievement motivation. The sample (n = 355) which was selected randomly consisted of 179 male and 176 female adolescents aged between 12- 15 years from 11 public lower secondary schools of Male', Maldives. The data were analysed using frequencies, descriptive statistics and Pearson product-moment correlation coefficient. The fmdings of the study revealed that the most prevalent maternal and paternal parenting style among the adolescents' parents of Male' was authoritative parenting style. It also indicated that adolescents of Male' had average self-esteem and high achievement motivation. Results of the correlation analysis indicated that there was a statistically significant and positive relationship between parental authoritativeness and adolescents' self-esteem and achievement motivation. It further revealed that there was a statistically significant but negative relationship between parental authoritarianism, permissiveness and neglect, and adolescents' selfesteem and achievement motivation.